Tribally-led mobile outreach: improving access to harm reduction services in one rural reservation community - Kelley, Allyson; Webb, Kellie; Hirchak, Katherine; Witzel, Morgan; Bajet, Kelsey; Posey, Sadie (Frontiers in Public Health, 2024)
American Indian and Alaska Native populations in the United States face significant disparities related to opioid use disorder and opioid-related mortality. Inequitable access to medications and harm reduction strategies due to structural, societal, and geographical factors prevent Tribal communities from obtaining needed services, and further contribute to the opioid epidemic. One Tribal Healing Center in the Rocky Mountain region identified mobile outreach to build upon existing opioid prevention, treatment, and harm reduction efforts. The Healing Center purchased a mobile outreach vehicle and worked with a combination of clinical staff, peer recovery support specialists, and Tribal elders to reach identified high-risk areas on the reservation. As of December 2023, the mobile outreach vehicle has disseminated 150 Narcan kits, 150 Fentanyl testing strips, 20 self-care kits, and 500 brochures detailing Healing Center services. Preliminary results from this formative evaluation demonstrate the success of MOV efforts and the process required to purchase and launch an MOV campaign.